Former les maîtres d’ouvrage de la transition écologique et climatique - Emmanuelle Bonneau; Catherine André (Projets de Paysage)
The master's degree in urbanism: landscape, environmental assessment and territorial projects (Urbanisme : paysage, évaluation environnementale et projets de territoire, UPEPT) at Université Bordeaux Montaigne, co-accredited with the École nationale supérieure d'Architecture et de paysage de Bordeaux (ENSAPBx), offers a training programme in project management support as a postgraduate course for landscape architects. Taking into account the transformation of the objectives and conditions of public action in urban planning and development due to the current injunction to engage in the ecological transition, this article sets out to identify the reciprocal contributions of landscape architecture and urban planning methods in support of this transition. The output from the pedagogical workshops of the UPEPT master’s programme supports and illustrates this demonstration.